PENERAPAN MODEL SINEKTIK BERBASIS PAPAN SERGU UNTUK MENINGKATKAN KETERAMPILAN MENULIS SUKU KATA SISWA KELAS I - Sri Wahyuni; Panca Dewi Purwati; Agus Yuwono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted due to the low ability to write syllables in the early grades of class 1 SDN Gayamsari 02 Semarang City with 28 students as subjects. Initial observations conducted at the pre-learning stage showed that many students had difficulty in writing syllables correctly. This study aims to: (1) describe the application of the Sergu Board, (2) Describe the results of the Sergu Board effectiveness test in learning to write syllables with the synectic model. Research methodology using the mix method. Research Results: (a) Implementing the Sergu Board in Learning Steps with the Synectic Model: Stage 1: Students are asked to describe a condition. Stage 2: Students are asked to make a direct analogy. Stage 3: Students are asked to make a personal analogy. Stage 4: The teacher asks questions that are dilemmatic/conflict. Stage 5: Students are asked to make further analogies. Stage 6: Students review the results of the analogy and learning assignments. (b) Results of the Sergu Board effectiveness test in learning to write syllables with the synectic model. Showing an increase in the average value of skills up 61% and the average value of creativity up 30% compared to the average value last year. The application of the synectic model based on the Sergu Board creates a creative and enjoyable learning atmosphere, thereby increasing student participation and literacy skills. This study concludes that the synectic model based on the Sergu Board is effective in improving syllable writing skills in grade I students.